(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
One of devices for removing char from syngas is a cloth-based filter. Char is mainly carbon black which is a good adsorbent and can be used for removing tar from syngas. When the latter passes through the filter, the char accumulates in it and adsorbs tar. In order to study effectiveness of this way of removing tar, samples of syngas for further analysis were taken twice, before and after the filter with char. A solid-phase adsorption (SPA) method for determining concentration of tar compounds has been chosen. The research showed that the filter for removing char from syngas proved quite cheap and effective in removing tar from syngas. Concentration of the total tar in the samples taken after the filter for removing char from syngas decreased by nearly 90% comparing to the total tar concentration in the samples taken before it. A solid-phase adsorption system consisting of amino-phase sorbent and activated coconut charcoal is a very convenient and effective device for sampling tar in syngas. If its concentration in syngas is high, light tar compounds are adsorbed on both sorbents. With a low concentration of tar in syngas, all compounds might be adsorbed only on the first sorbent.